Rancang Bangun Sistem Informasi Desa Wisata Bumirejo Berbasis Web - Apriliya Kurnianti; Bagus Pribadi (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2022)
At first, Bangunkerto Village was an area consisting of 3 (three) Kelurahan namely: Ganggong, Selobonggo, and Wonosari Villages. Based on the edict of the Yogyakarta Special Region Government issued in 1946 regarding the Village Administration, the Kelurahan-Kelurahan was then merged into one autonomous village with the name Bangunkerto Village. Bangunkerto Village is a Cultural Village which has both physical and non-physical potential. One of the hamlets from Bangunkerto village that has the potential of a tourism village is Bumirejo hamlet. The existence of tourist villages is currently a concern of the government in increasing economic equity and reducing the Gini ratio of Indonesia. Bumirejo Hamlet has tremendous economic potential with its natural wealth and superior products. With the existing potential, Bumirejo hamlet wants to develop this potential into a tourist village. The development of the tourist village, in addition to development, also requires promotional media as an intermediary to introduce natural beauty and its superior products. The purpose of this service is to create a website that can be a solution as a media for promotion and economic improvement in Bumirejo Hamlet. the methods used in the service include: 1). Problem identification, 2). Implementation stage, 3). Evaluation